The Transformation Problem: Labor Theory or Command Theory of Value?. Issue 3 (2nd October 2021) - Finger, Barry
Abstract : Values and prices are two dimensionally different measurements of the weights of commodities in exchange: one expressed in units of time, the other in money. Between the two there is a factor of proportionality such that the annual sum of activated productive labor time is re-expressed as a definite quantity of monetary output. This is maintained both at the level of individual commodity units in their exchange with money and for the totality of commodity units turned over in a given period of time. This factor of proportionality obviously fluctuates over time. The exchange of commodities at prices proportional to values does not also imply that the sum of values should ever be equal to the sum of prices, nor the sum of surplus values be equal to the sum of profits. Yet Marx, in Capital III, nevertheless elaborates a specific analytical break between the conditions of exchange that dominate 'simple' commodity production and capitalist commodity production, but claims to have reconciled the two by invoking these criteria. He does so by constructing an alternative system to account for the average rate of profit in which the value of capitalist commodities are represented, not by their embodied labor content, but by the labor content of the money commodity against which they are exchanged prior to becoming future components in the circuit of productive capital. This paper offers an alternative solution to the transformation problem and incorporates the average rate of profit within the pricing framework of Capital I. It seeks to show why other attempts, both hostile and friendly, to resolve the issue along the proposed lines of Capital III necessarily replace the labor theory of value with a command theory of value. In this, Marx failed to transcend the classical dilemma and became, instead, a prisoner to it.